2017
DOI: 10.3390/fermentation3040059
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Arthrospira platensis (Spirulina) Growth: From Laboratory Scale to Pilot Scale

Abstract: Arthrospira platensis (Spirulina) is the most cultivated microalga worldwide. Improving its cultivation in terms of biomass productivity, quality, or production cost could significantly impact the Spirulina industry. The objectives of this paper were defined as to contribute to this goal. Spirulina biomass productivity was investigated through medium choice. A modified Zarrouk's medium was selected as it gave higher final dry weights and longer sustained growth than Hiri's and Jourdan's media. Then, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 25 publications
3
53
1
2
Order By: Relevance
“…Culture volumetric productivity varied between 0.04 and 0.08 g/L/day (overall mean value: 0.06 ± 0.012 g/L/day; Table 1), with the highest productivities recorded at the days 0-6 for the F phase and at the days 42-46 for the R phase (0.08 ± 0.002 and 0.07 ± 000.2 g/L/day, respectively). A negative correlation between productivity rate and initial culture concentration at each semi-continuous cycle was found (r = −0.83; p < 0.05), in accordance with previous reports that underline a reciprocal shadowing effect occurring at high cell densities [8,52]. Average productivity did not differ significantly between the two phases (mean value: 0.06 ± 0.016 and 0.06 ± 0.010 g/L/day for F and R phase, respectively).…”
Section: Culture Productivity and Harvesting Efficiencysupporting
confidence: 91%
See 2 more Smart Citations
“…Culture volumetric productivity varied between 0.04 and 0.08 g/L/day (overall mean value: 0.06 ± 0.012 g/L/day; Table 1), with the highest productivities recorded at the days 0-6 for the F phase and at the days 42-46 for the R phase (0.08 ± 0.002 and 0.07 ± 000.2 g/L/day, respectively). A negative correlation between productivity rate and initial culture concentration at each semi-continuous cycle was found (r = −0.83; p < 0.05), in accordance with previous reports that underline a reciprocal shadowing effect occurring at high cell densities [8,52]. Average productivity did not differ significantly between the two phases (mean value: 0.06 ± 0.016 and 0.06 ± 0.010 g/L/day for F and R phase, respectively).…”
Section: Culture Productivity and Harvesting Efficiencysupporting
confidence: 91%
“…Daily evaporation of the A. platensis BEA 1257B culture during the course of the experiment (mean value: 3.9 ± 1.0 mm for F and 3.0 ± 1.1 mm for R phase; p < 0.01) was lower than that recorded in open ponds located in arid or semi-arid areas ( 6 mm), likely due to an increased relative humidity in the surrounding atmosphere enabled from the greenhouse barrier [8,26,34]. This water-loss limitation accounts for more than a one-third reduction in the water demand due to evaporation, this latter being estimated around the 35% of the total water demand for freshwater microalgae cultivation [56].…”
Section: Culture Parametersmentioning
confidence: 67%
See 1 more Smart Citation
“…Salunke et al (2016), regarded that urea is more effective than KNO 3 for S. platensis. The previous studies demonstrated that the availability and concentration of nitrogen source influence the microalgal proteins content (Markou, 2015;Li et al, 2016) Delrue et al (2017 reported that when Spirulina was cultivated for 40 days cultivation in a 1000L-photobioreactor during spring 2015. This period of cultivation helped to increase the possibility of Spirulina growth in the photobioreactor and improving biomass productivity.…”
Section: Discussionmentioning
confidence: 99%
“…In some trace minerals (Mn, Zn, and Se), the amounts were lower compared to the three sources previously mentioned [47]. The variation in microalgae biomass composition often results from different culture conditions such as the stress parameters (temperature and light intensity, among others) used for its cultivation [48]. Some studies have compared several environmental factors (nitrogen concentrations, pH, CO 2 , etc.)…”
Section: Nutritional Composition Of Spirulinamentioning
confidence: 95%